Understanding the tumor microenvironment in head and neck squamous cell carcinoma. Issue 6 (6th June 2022) - Rad, Habib Sadeghi; Shiravand, Yavar; Radfar, Payar; Ladwa, Rahul; Perry, Chris; Han, Xiaoyuan; Warkiani, Majid Ebrahimi; Adams, Mark N; Hughes, Brett GM; O'Byrne, Ken; Kulasinghe, Arutha
Abstract: Head and neck squamous cell carcinoma (HNSCC) represents a heterogeneous group of tumors. While significant progress has been made using multimodal treatment, the 5‐year survival remains at 50%. Developing effective therapies, such as immunotherapy, will likely lead to better treatment of primary and metastatic disease. However, not all HNSCC tumors respond to immune checkpoint blockade therapy. Understanding the complex cellular composition and interactions of the tumor microenvironment is likely to lead to new knowledge for effective therapies and treatment resistance. In this review, we discuss HNSCC characteristics, predictive biomarkers, factors influencing immunotherapy response, with a focus on the tumor microenvironment. Abstract : This manuscript describes the tumor microenvironment of head and neck cancers that is integral for understanding effective therapies.